Interdisciplinarne tematske zbirke podatkov kot platforma povezovanja raziskovalcev - Bezjak, Sonja (Teorija in praksa, 2023)
Environmental data can be an important element in advancing knowledge to address the challenges and questions we face at the beginning of the 21st century. This article reflects on how to conceptualise and what to include in an environmental database to engage different stakeholders and contribute to building a broad community of stakeholders. In our dataintensive era, data archives are a platform for connecting data producers and data users, researchers, research infrastructures, public services, citizen scientists and others. Accessible and transparent data and other data-related services contribute to interdisciplinary collaboration and the implementation of inclusive open science
Keywords: CESSDA; citizens's science; climate change; data centres; družboslovni koncepti; environment; Informacije; občanska znanost; okolje; podatkovni arhivi; Podnebne spremembe; raziskovalni podatki; research data; social science concepts